Comparison of Diabetogenic and Lipid Profile Among Vitamin D Deficient and Non-deficient Male Subjects - Khan, Sikandar Hayat; Khan, Abdul Rahim; Shahid, Rahat; Manzoor, Robina (Archives of Clinical and Biomedical Research, 2020)
Objective: To evaluate diabetogenic and lipid profiles among subjects with or without vitamin D deficient male subjects. Design: Cross-sectional analysis Place and duration of study: From Jan- 2018 to Dec- 2018 at PNS HAFEEZ hospital Islamabad Subjects and methods: From a target population of adult male patients selected after several exclusion, we had a final total sample size of 133, which were evaluated among two groups formulated based upon whether having vitamin D deficiency or otherwise. We further compared diabetic and lipid indices including fasting plasma glucose, glycated hemoglobin (HbA1c), total cholesterol, fasting triglycerides, LDL cholesterol and HDL cholesterol among the vitamin D deficient group and vitamin D non-deficient groups by using Independent sample t-statistics. Results: HbA1c levels were higher in subjects with vitamin D deficiency [Mean: 7.43% (+2.45), n=87] in comparison to non-vitamin D deficient subjects [Mean: 6.54% (+1.67), n=45], (p=0.029). Fasting plasma glucose levels were higher in subjects with vitamin D deficiency [Mean: 8.12 mmol/L (+4.05), n=86] in comparison to non-vitamin D deficient subjects [Mean: 6.88 mmol/L (+2.85), n=43], (p=0.074). Lipid parameters did not demonstrate statistical significance among subjects with or without vitamin D deficiency. Conclusion: HbA1c and fasting plasma glucose levels were higher among subjects with vitamin D deficiency in comparison to non-vitamin D deficient male subjects.